Caregiver's Knowledge about Childhood Pneumonia: A Study from Rural Areas and Urban Slums of Lucknow - Anurag Minz; Monika Agarwal; Jai Veer Singh; Vijay Kumar Singh; Rajesh Sahu (Medsci Publications, 2019)
Background: India bears highest burden of childhood morbidity and mortality due to childhood pneumonia. The study was con- ducted with aim to assess caregivers' knowledge about signs/symptoms of childhood pneumonia and their perception about its risk factors and preventive measures. Methodology: This community based cross sectional study was carried out among 568 caregivers of 1065 under-five children. A pretested, semi-structured questionnaire was used to collect in- formation about bio-social profile, caregivers' knowledge about signs & symptoms, danger signs, risk factors and preventive measures of pneumonia. Results: Majority of the respondents (88.7%) identified "cough/cold" as sign and symptom of pneumonia, followed by "chest in-drawing" (85.7%) and "fast/difficult breathing" (77.8%). Only few caregivers (9.3%) perceived "fast/difficult breathing" as danger sign and only 12% and 16.1% respectively had adequate knowledge about risk factors and preventive measures of child- hood pneumonia. The study found statistically significant associa- tion between parent's education status and knowledge about risk factors, preventive measures and ability to recognize early danger signs of childhood pneumonia. Conclusions: The study identified significant lack of knowledge about childhood pneumonia among caregivers. Strengthening of IMNCI and community-based health education programs need to be promoted to ensure better health practices and appropriate care seeking for childhood pneumonia.